Revising England's social tables once again - Allen, RC (University of Oxford, 2016)
In the 1980s, Lindert and Williamson famously revised the social tables of King, Massie, Colquhoun, Smee, and Baxter that traverse the British industrial revolution. This paper extends their work in three directions: Servants are removed from middle and upper class households in the tables of King, Massie, and Colquhoun and tallied separately, estimates are made for the same tables of the number and incomes of women and children employed in the various occupations, income estimates are broken down into rents, profits, and employment income. These extensions to the tables allow variables to be computed that can be checked against independent estimates as a validation exercise. The tables are retabulated in a standard format to highlight the changing social structure of Britain during the industrial revolution. Changes in the social structure, the evolution of incomes by classes, and the pace of structural transformation are revealed.